75.0k views
0 votes
Solve for x -3x + 3 < 6



2 Answers

3 votes

Answer and Step-by-step explanation:


\huge\boxed{x>-1}

→ Subtract 3 from both sides:


-3x+3-3<6-3

→ Simplify:


-3x<3

→ Multiply both the sides by -1 (reverse the inequality):


(-3x)(-1)>3(-1)

→ Simplify:


3x>-3

→ Divide both sides by 3


(3x)/(3)>(-3)/(3)

→ Simplify:


x>-1

User Zakher Masri
by
5.4k points
3 votes

Answer:

X>-1

Explanation:

Isolate x on one side of the equation.

-3x+3-3<6-3 (Subtract 3 from both sides.)

6-3 (Solve.)

6-3=3

-3x<3

(-3x)(-1)>3(-1) (Multiply by -1 from both sides.)

3(-1) (Solve.)

3*-1=-3

3x>-3

3x/3>-3/3 (Divide by 3 from both sides.)

-3/3 (Solve & Simplify.)

-3/3=-1

X>-1

In conclusion, the final answer is X>-1.

User Ted Mielczarek
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.